Determination of Parameters of a Cold Front of the Cyclone Kyrill from Synchronous Measurements of Atmospheric Pressure and Muon Flux - Sopin, A. O.; Yampolski, Yu. M. (Видавничий дім «Академперіодика», 2012)
Results are presented of joint analysis of variations in the surface pressure and muon flux observed at the Low Frequency Observatory of the Institute of Radio Astronomy NAS–Ukraine during the passage of the Kyrill storm over Europe. A time lag between the processes has been found and explained. The commonly accepted model of a cold cyclonic front is used to estimate space and time characteristics of the cyclonic front, specifically, the slope angle and horizontal dimension. The results are in good agreement with the characteristic parameters for cold fronts known from the literature.